ASUHAN KEPERAWATAN PENERAPAN KOMUNIKASI TERAPEUTIK PADA KLIEN ISOLASI SOSIAL DI RSJS DR SOEROJO MAGELANG - Alfiyah Nur Azijah; Arni Nur Rahmawati (Sekolah Tinggi Pariwisata Mataram, 2022)
Social isolation is a condition where a person experiences or is unable to interact with other people around him. The purpose of this study was to provide nursing care to clients with Social Isolation in the Inpatient Room of Prof. DR. Soerojo Mental Hospital Magelang. The method used by the researcher is a qualitative study using case research using a nursing process approach in 1 patient experiencing social isolation. The process of collecting data by interviewing, observing and viewing the patient's medical records. Data analysis was carried out by data collection and data reduction. The results of the study showed that all interventions were successfully carried out and nursing problems were resolved, indicated by the patient being able to recognize the cause of ISOS and get acquainted, talk about 1 topic or get acquainted with two people, talk in social groups and talk for help and answer questions using the application of therapeutic communication in the isolation implementation strategy. social. Therapeutic communication is referred to as an interpersonal bond between nurses as caregivers to their clients, so that nurses and clients get experience practicing together to improve the emotional experiences experienced by clients so that a therapeutic bond is realized. So it can be concluded that the application of therapeutic communication to social isolation clients is effective in increasing social interaction in social isolation nursing problems.